PPN & PPNBM: SUBJEK, OBJEK SERTA MEKANISME DI INDONESIA - Elvina Zailanty Harahap; Muhammad Hafizhan Fakhri, Ocha Pratika, Dini Vientiany (JEBIMAN : Jurnal Ekonomi, Bisnis, Managemen dan Akuntansi, 2024)
The aim of the research is to increase information regarding VAT and PPnBM. This research uses descriptive research with a qualitative approach. VAT is a tax on consumption of goods and services in the customs area which is imposed in stages in each production and distribution channel. PPnBM is a tax levied on the delivery of BKP which is a luxury item. The VAT rate is regulated as follows: 10% .0%, specifically VAT on exports of Taxable Goods. The PPnBm rate is set at a minimum of 10% and a maximum of 200%. The basis for PPnBM is based on Law Article 8 No. 42 of 2009 concerning the 3rd Amendment to Law no. 8 of 1983